Al-Qur’an sebagai Basis Aktivitas Pendidikan: Kontribusi Tafsir Surat Luqman karya K.H. Abdulchalim Iskandar - Rohmana, Jajang A (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
This article focuses on the issue of education in the Qur’anic commentary which is practiced into educational activities. The object of the study is a Sundanese book, Tafsir Surat Luqman (1955) by K.H. Abdulchalim Iskandar (1887-1962), a national hero from Majalengka. This Sundanese pegon book is a Qur’anic commentary of Sūrah Luqmān/31. Abdulchalim comments this sūrah and served the commentary as the basis for his educational activities from the colonial period to the Sukarno era. He founded some educational institutions such as Madjlisoel ‘Ilmi, Madrasah Jam’ijjat I’anat al-Muta’allimin, Madrasah Persjarikatan Oelama and Santi Asromo. Through Fairclough’s critical discourse analysis approach, this study confirms that Abdulchalim’s commentary of the Qur’an cannot be separated from his educational activities through the educational institution. His aim is how the indigenous people get a good education so that they have noble character and self-employed. This commentary of Surah Luqman is an example of how the verses of the Qur’an can be an inspiration in developing activities through the formation of educational institutions. It is a real practice of a national hero in practicing the Qur’anic verses bring into the reality.